The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1516-35982012001200003
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and anatomical characteristics of tree-shrub legumes in the Forest Zone in Pernambuco state, Brazil

Abstract: -The objective of this study was to characterize the nutritional value of forage legumes Mimosa caesalpiniifolia (Benth.), Bauhinia cheilantha (Bong.) and Leucaena leucocephala (Lan.) and evaluate the anatomy of plants incubated and not incubated in the rumen. The experiment was conducted from September 2007 to November 2008. The experimental plot consisted of three useful plants, totaling three plots per block, and four repetitions. Plants were cut at 1 m height at intervals of 70 days; samples of leaf plus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, our results suggested that the leaching rates of K + seem to be driven by the presence of cellular structures associated with resource storage (parenchyma) and transfer (sieve cells) [30], which, in turn, is consistent with the RDA results for the BWA% of the species L. leucocephala, where potassium was the most influenced by the bark absorption capacity. Researchers studying L. leucocephala, Bauhinia cheilantha, and Mimosa caesalpiniifolia observed that the abaxial epidermis was thinner than the adaxial one, and the stomata on the abaxial surface were numerous, with the palisade parenchyma juxtaposed, arranged in a single layer with few intercellular spaces [32]. The presence of K + is the result of the leaching of this ion from the canopy itself [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results suggested that the leaching rates of K + seem to be driven by the presence of cellular structures associated with resource storage (parenchyma) and transfer (sieve cells) [30], which, in turn, is consistent with the RDA results for the BWA% of the species L. leucocephala, where potassium was the most influenced by the bark absorption capacity. Researchers studying L. leucocephala, Bauhinia cheilantha, and Mimosa caesalpiniifolia observed that the abaxial epidermis was thinner than the adaxial one, and the stomata on the abaxial surface were numerous, with the palisade parenchyma juxtaposed, arranged in a single layer with few intercellular spaces [32]. The presence of K + is the result of the leaching of this ion from the canopy itself [33].…”
Section: Discussionmentioning
confidence: 99%